Rasio Keuangan dan Harga Saham Perusahaan di Bursa Efek Indonesia - Yulia Bentari Kahitela (Politeknik Ganesha Medan, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of financial ratios on stock prices. The ratios used are DER, CR, PER, ROA and NPM. The population of this study are all non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2021-2022. Purposive sampling is used in the research sampling technique. Multiple linear regression analysis with the SPSS 25 program was used as an analytical technique. Based on an analysis of 284 company years, this study concludes that DER, PER and ROA have a positive effect on stock prices. CR has a negative effect on stock prices and NPM has proven to have no effect on stock prices. The results of this study indicate that an increase in DER, PER and ROA is in line with an increase in stock prices. Conversely, each increase (decrease) in CR causes a decrease (increase) in the share price.